SEGMENTASI PASAR KOPI BUBUK BALI BANYUATIS DI KOTA DENPASAR - Ni Ketut Lasmini (Forum Manajemen STIMI Handayani Denpasar, 2012)
This study aims to identify the Kopi Bubuk Bali Banyuatis market. Themarket segments of Kopi Bubuk Bali Banyuatis is formulated through the data analysisof consumer’s behavioral and psychographic by the method of Cluster Analysisusing the K-Means Cluster subsequent cross tabulated with demographics. Theresults: Segment-1, (42.9%), predominantly male, middle-aged, high schooleducation, self-employed and middle-income. Consumer behavior, consumptionlevels often, the readiness to buy is very high because they understood the product,be positive about the product, and its benefits. Psychographic consumer, includingthe category of active, modern, optimistic, and relatively established. Incomerate varies from lower class to upper class. Such a potential segment as markettarget. Segment-2, (35.7%), male-dominated, younger age, high school education,private employees, and middle-income.Consumer behavior, consumption levels arerare, the readiness to buy is moderate, attitudes toward products and its benefits ispositive. Psychographic consumer, simple and optimistic. Considerable potential asa market target after segment-1. Segment-3, (21.4%), male-dominated, middle-aged,high school education, private employees, and middle-income.Consumer behavior,consumption levels are very rare, low readiness to buy, attitude towards the productand itsbenefits is negative. Psychographic consumer, logical, normative, homely andthus less potential as a market target . Based on size and market structure and theobjectives and resources of the company, the segment-1 was chosen as the targetmarket by the company. By understanding market segmentation and know its customers, the policy will beeasier to be taken in marketing the products. Selection of promotion strategies willbe more focused, able to provide satisfaction and increase customer loyalty.